2019
DOI: 10.1007/s40121-019-0232-7
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Epidemiology of Infectious Endocarditis in the Intravenous Drug Abuse Population: A Retrospective Study

Abstract: Introduction The microbial epidemiology differs between infective endocarditis (IE) patients with and without a history of injection drug use. We set out to determine the prevalence and microbial epidemiology of infective endocarditis in our region, the Southeastern USA, to determine if any changes need to be made in empiric antimicrobial treatment. Methods The electronic medical record was reviewed for patients with IE between January 2013 and July 2017, which revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
4
0
6
Order By: Relevance
“…With the ongoing opioid epidemic and increasing prevalence of injection drug use, the risks of MRSA bacteremia and IE are on the rise [ 11 ]. This study found that obtaining a TEE routinely after a TTE might not be cost-effective in this patient population of PWID with proven native-valve MRSA IE.…”
Section: Discussionmentioning
confidence: 99%
“…With the ongoing opioid epidemic and increasing prevalence of injection drug use, the risks of MRSA bacteremia and IE are on the rise [ 11 ]. This study found that obtaining a TEE routinely after a TTE might not be cost-effective in this patient population of PWID with proven native-valve MRSA IE.…”
Section: Discussionmentioning
confidence: 99%
“…Подобно ИЭ в общей популяции, S. aureus является микроорганизмом, наиболее часто вызывающим ИЭ у ПИН (до 77,2 % случаев ИЭ у потребителей наркотиков против 39,6 % среди пациентов общей популяции) [8,21,22]. Это связано с более высоким уровнем колонизации кожи S. aureus (вероятно, из-за частого нарушения её целостности) у ПИН по сравнению с лицами, использующими наркотики только перорально.…”
Section: инфекционный эндокардит у лиц применяющих внутривенные нарко...unclassified
“…Нарушение кожного барьера иглой обеспечивает прямое попадание микроорганизмов в кровоток. В работах, посвященных анализу заболевания у ПИН, опубликованных в последние годы, прослеживается преобладание метициллин-чувствительного штамма S. aureus над метициллин-резистентным [18,[21][22][23]. W. Lorson et al (2019) подчеркивают этиологическое значение метициллин-резистентных штаммов S. aureus и Pseudomonas в развитии ИЭ у ПИН и необходимость применения антибиотиков с активностью в отношении этих возбудителей [22].…”
Section: инфекционный эндокардит у лиц применяющих внутривенные нарко...unclassified
See 1 more Smart Citation
“…Future research with SEA patients with IVDU is needed to identify how to best support these patients during first and subsequent readmissions, and to better understand why these patients are at higher risk of readmission. Finally, there may be clinically important differences in microbiological etiology of SEA between these two groups, including differences in the incidence of Pseudomonas infections, which could inform empiric antibiotic choice [1,25].…”
Section: Plos Onementioning
confidence: 99%